2020
DOI: 10.3390/genes11020225
|View full text |Cite
|
Sign up to set email alerts
|

Working on Genomic Stability: From the S-Phase to Mitosis

Abstract: Fidelity in chromosome duplication and segregation is indispensable for maintaining genomic stability and the perpetuation of life. Challenges to genome integrity jeopardize cell survival and are at the root of different types of pathologies, such as cancer. The following three main sources of genomic instability exist: DNA damage, replicative stress, and chromosome segregation defects. In response to these challenges, eukaryotic cells have evolved control mechanisms, also known as checkpoint systems, which se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 249 publications
(366 reference statements)
0
30
0
1
Order By: Relevance
“…It is unclear whether this leakage underlies a low level of active forks or terminally arrested forks that do not signal to the checkpoint. Indeed, several studies have shown that replication completion at some loci in the genome, notably CFSs, can be delayed after the S phase, particularly after replication stress; thus, replication intermediates persist until G2 and mitosis [37,66]. A recent study from Lafarga and collaborators identified the RNA-binding protein TIAR as a novel component of a G2/M checkpoint that prevents cells with under-replicated or damaged DNA from entering mitosis.…”
Section: Mechanisms Protecting Against Replication Stress and Under-rmentioning
confidence: 99%
See 1 more Smart Citation
“…It is unclear whether this leakage underlies a low level of active forks or terminally arrested forks that do not signal to the checkpoint. Indeed, several studies have shown that replication completion at some loci in the genome, notably CFSs, can be delayed after the S phase, particularly after replication stress; thus, replication intermediates persist until G2 and mitosis [37,66]. A recent study from Lafarga and collaborators identified the RNA-binding protein TIAR as a novel component of a G2/M checkpoint that prevents cells with under-replicated or damaged DNA from entering mitosis.…”
Section: Mechanisms Protecting Against Replication Stress and Under-rmentioning
confidence: 99%
“…ATR was shown to be recruited to centromeres in an R-loop-dependent manner, where it activates Aurora B to promote faithful microtubule binding and subsequent chromosome segregation [74]. The tight coordination between the DDR pathways and cell cycle checkpoints throughout the S phase and mitosis is thus key to preventing genome instability [66].…”
Section: Mechanisms Protecting Against Replication Stress and Under-rmentioning
confidence: 99%
“…Thus, accumulating evidence has suggested the existence of mitotic DSB repair, and this is further supported by recent results showing the existence of mitotic DNA repair synthesis [ 18 , 20 , 27 , 28 ]. Sister chromatid non-disjunction, which results in ultrafine bridges (UFBs) in anaphase, should be repaired in mitosis, and resolution of UFBs requires DNA polymerase delta subunit 3 (POLD3)-dependent unscheduled DNA synthesis, so this could provide evidence for mitotic DSB repair in somatic cells [ 20 ].…”
Section: Introductionmentioning
confidence: 68%
“…Replication stress is a phenomenon which has serious implications for genome duplication, genome division, and genome stability [ 1 ]. Replication stress is generally described as the inhibition or slow-down of DNA replication, which leads to a highly dangerous accumulation of DNA damage in a cell.…”
Section: Introductionmentioning
confidence: 99%